DAMPAK MOTIVASI KERJA, IKLIM ORGANISASI, LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN LEMBAGA PERKREDITAN DESA PECATU - Wibiseno, Qisthio; Dewi, I Gusti Ayu Manuati (E-Jurnal Manajemen; Vol 7 No 12 (2018)DO - 10.24843/EJMUNUD.2018.v07.i12.p14, 2018)
This research aims to determine the influence of work motivation, organizational climate, and work environment to job satisfaction of Lembaga Perkreditan Desa (LPD) Adat Pecatu employee . This research uses saturated sampling technique in which the entire population consisting of all 49 employees of LPD Adat Pecatu that used as research sample . Research data is collected using the questionnaire which co ntains the indicators of the research variable, consists of work motivation, organizational climate, work environment, and job satisfaction related questions. Data analysis technique used is multiple linear regression analysis. The results of the analysis showed that work motivation and work environment does not have significant influence towards job satisfaction, however, organizational climate have a positive  and significant influence towards job satisfaction employee of LPD Adat Pecatu .